An Efficient Co-Precipitation Synthesis of BaZr1-xCoxO3 Nanoparticles: Structural, Optical and Magnetic Properties - D. EL-Said Bakeer; Abdel-Hamed Sakr; Hussien Motaweh; Walaa El-Sokary (Journal of Nanostructures, 2019)
In this study, BaZr1-xCoxO3 nanoparticles, x = 0.00, 0.04, 0.06, 0.08, 0.10 and 0.20, are synthesized through co-precipitation method. Therefore, structural, optical and magnetic properties have been investigated. The cubic perovskite structure is confirmed by X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopic measurements. The average crystallite size and micro strain are calculated by Williamson-hall analysis and they have been found to increase by increasing the Co2+ content. More emphasis is given for the calculation of the optical parameters from UV–visible absorption spectra. The optical bandgap is found to be decreasing; on the other hand Urbach energy increases with the increase in Co2+ content. The refractive index of the samples obeys the single-oscillator model and the dispersion parameters such as single oscillator energy, dispersion energy, and lattice dielectric constant are calculated and their variations with Co2+ content are reported. The undoped BaZrO3 nanoparticles exhibits unexpected superparamagnetic behavior and ferromagnetic hysteresis at room temperature for BaZr1-xCoxO3 , x=0.10 and 0.20. With the increase in the Co2+ content, the concentration of oxygen vacancies increases and as a result the magnetic properties are improved. Thus, the most significant result of the present work is the modification of optical constants and the improvement of magnetic properties of BaZrO3 nanoparticles by partial Co2+ substitution.